The mediating role of incentives in association between leadership attention and self-perceived continuous improvement in infection prevention and control among medical staff: A cross-sectional survey - Wang, Lu; Zhang, Dandan; Liu, Junjie; Tang, Yuqing; Zhou, Qian; Lai, Xiaoquan; Zheng, Feiyang; Wang, Qianning; Zhang, Xinping; Cheng, Jing (Frontiers in Public Health, 2023)
Objectives: Promoting improvement in Infection Prevention and Control (IPC) is an important part of improving the quality of care. The influence of leadership attention and incentives on the self-perceived continuous improvement in IPC has drawn a lot of attention, but relevant academic research is still lacking. The objective of this study is to explore the effect of leadership attention on self-perceived continuous improvement in IPC among medical staff and its underlying mechanisms. Method: The 3512 medical staff from 239 health facilities in Hubei, China, were surveyed online during September 2020. Data on leadership attention, incentives, and improvement in Infection Prevention and Control were collected using self-administered questionnaires. Correlation analysis was used to analyze the relationship between leadership attention, incentives, and improvement in Infection Prevention and Control. Amos 24.0 was used to analyze the mediating role. Results: The scores of leadership attention, incentives and self-perceived continuous improvement in Infection Prevention and Control were all high. The score of leadership attention was the highest (4.67±0.59), followed by self-perceived continuous improvement (4.62±0.59) and incentives in Infection Prevention and Control (4.12±0.83). Leadership attention positively affected self-perceived continuous improvement in Infection Prevention and Control (β =0.85, 95% CI = [0.83, 0.87]). Moreover, incentives partially mediated the effect of leadership attention on self-perceived continuous improvement in Infection Prevention and Control among medical staff (β = 0.13, 95% CI = [0.12, 0.15]). Conclusion: Leadership attention positively affects self-perceived continuous improvement in Infection Prevention and Control among medical staff, and incentives mediates this relationship. The present study has valuable implications for self-perceived continuous improvement in Infection Prevention and Control from the perspective of leadership attention and incentives.